El latín del Llibre de la Cort del Justícia d'Alcoi - Ferragut, Concha (2012)
En este artículo analizamos el latín empleado en la redacción del Llibre de la Cort del Justicia d’Alcoi, documento que supone el testimonio más antiguo de una corte judicial del reino de Valencia conservado en papel y constituye un fuente documental de extraordinaria riqueza para el estudio de la lengua latina y de su función, similar al resto de territorios de la Península Ibérica y de Europa en general, en la Corona de Aragón durante el periodo bajomedieval.
In this article we analyze the Latin used in the writing of the Llibre de la Cort del Justícia d’Alcoy, a manuscript that constitute the oldest example conserved in paper of a judicial court of the Kingdom of Valencia, and it constitutes an extraordinary valuable documentary source for the study of the Latin language and its role in the Crown of Aragon, similar to other territories of the Iberian Peninsula and Europa in general, during the late medieval period.
Keywords: Llibre de la Cort del Justícia d'Alcoi; Lengua latina; Historia medieval